MATLAB modeling of simple propulsion system / Muhamad Asri Salleh - Salleh, Muhamad Asri (2007)
This paper presents the dynamic characteristic of electric propulsion systems and explains why these developments are economically and operationally desirable. It describes the application of electric motors and their converters into a ship's propulsion system and discusses the characteristics and attributes of each system's operation and control.